Potensi Sumber Daya Manusia di Era Otonomi Sekolah - Oentoe, Fientje J.A. (Jurnal Aplikasi Manajemen, 2009)
The principals potentials are able to actualizations in four levels of competence are: (1)technical competence, (2) interpersonal competence, (3) instructional competence, and (4) political competence. Teachers' potential to actualization in: (1) to understand the existence of students from biological, psychological and intellectual views,(2) tobe fasilitators, (3) in general, to conduct some researches concerning with the subject they teach. The students' potential to actualizations in: (1) propose their opinions and suggestions in intra as well as extracurricular activities, (2) to make some decisions that have non academic characteristics.